A Descriptive Study to Assess the Knowledge Regarding Hand Hygiene among Students of Selected Nursing College in Ludhiana, Punjab (International Journal of Nursing Education, 2020)
Introduction: Hand hygiene is defined as any method that removes or destroys micro-organism on hands.It is well-documented that the most important measure for preventing the spread of pathogens is effectivehandwashing.Aims: To assess the knowledge regarding hand hygiene among students of selected nursing college and toseek the knowledge score with selected demographic variables.Material and Method: An descriptive research approach was used to assess the knowledge regardinghand hygiene. Convenient sampling technique was used to select 60 nursing students. A self structuredquestionnaire method was used to assess the knowledge of students regarding hand hygiene.Conclusion: Based on the findings of the study it can be concluded that 35% of nursing students havemoderately adequate knowledge and 65% of students have inadequate knowledge regarding hand hygiene.